2014
DOI: 10.1016/j.immuni.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The Coinhibitory Receptor CTLA-4 Controls B Cell Responses by Modulating T Follicular Helper, T Follicular Regulatory, and T Regulatory Cells

Abstract: Summary The receptor CTLA-4 has been implicated in controlling B cell responses, but the mechanisms by which CTLA-4 regulates antibody production are not known. Here we showed deletion of CTLA-4 in adult mice increased Tfh and Tfr cell numbers, and augmented B cell responses. In the effector phase, loss of CTLA-4 on Tfh cells resulted in heightened B cell responses, whereas loss of CTLA-4 on Tfr cells resulted in defective suppression of antigen-specific antibody responses. We also found that non-Tfr Treg cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
424
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 354 publications
(456 citation statements)
references
References 39 publications
18
424
1
1
Order By: Relevance
“…Despite down-regulation of some eTreg-associated genes, CD25 − Tfr cells maintained their expression of the majority of suppressive molecules, most critically CTLA-4, which we and others have demonstrated to have a key role in Tfr-dependent control of Tfh function (41)(42)(43). Notably many of the genes down-regulated in CD25 − Tfr cells, such as Klrg1, Itgae (CD103), Prdm1 (BLIMP-1), Il10, and Gzmb (Granzyme B), are IL-2-dependent (34).…”
Section: Discussionmentioning
confidence: 81%
“…Despite down-regulation of some eTreg-associated genes, CD25 − Tfr cells maintained their expression of the majority of suppressive molecules, most critically CTLA-4, which we and others have demonstrated to have a key role in Tfr-dependent control of Tfh function (41)(42)(43). Notably many of the genes down-regulated in CD25 − Tfr cells, such as Klrg1, Itgae (CD103), Prdm1 (BLIMP-1), Il10, and Gzmb (Granzyme B), are IL-2-dependent (34).…”
Section: Discussionmentioning
confidence: 81%
“…However, regulatory CD4 + T cells are also found within GCs,235 and recent studies have shown that a subset of CXCR5 +  FoxP3 +  CD4 + Treg cells, termed T follicular regulatory (Tfr) cells, are generated as immune responses are induced and localize to the GC to control the GC response 236, 237, 238. In mice, Tfr cells have been shown to reduce antibody production and the number of GC B cells, antigen‐specific B cells, and plasma cells 236, 237, 238, 239, 240, 241. Multiple stages of the B‐cell differentiation process are inhibited, from initial B‐cell activation to the generation of class‐switched B cells and plasma cells.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
“…Multiple stages of the B‐cell differentiation process are inhibited, from initial B‐cell activation to the generation of class‐switched B cells and plasma cells. Tfr cells also inhibit Tfh cell expansion, differentiation, and production of cytokines such as IL‐21 and IL‐4 239, 240, 242. Human Tfr cells (defined as CD127 −  CD25 +  CXCR5 +  CD4 + cells) have likewise been shown to reduce antibody production in in vitro Tfh:B cell co‐culture assays 243.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
See 2 more Smart Citations